Prevalence and Antimicrobial Resistance of Salmonella in Poultry Products in Central Ethiopia - Isayas Asefa Kebede; Tefari Duga (Veterinary Medicine International)
Salmonellosis is a bacterial infection caused by salmonella, a member of the Enterobacteriaceae family. From December 2021 to May 2021, a cross-sectional study was carried out to isolate Salmonella from poultry farms in the towns of Bishoftu and Adama and to determine the antimicrobial susceptibility frequency of the isolates. A total of 384 samples were tested for the presence of Salmonella, including 259 feces, 56 eggs, and 69 types of meat, using the ISO, 2002 standard procedures. The raw data were organized, coded, and entered into an Excel spreadsheet before being analyzed with STATA via descriptive analysis with chi-square. From 384 collected samples, 62 (16.15%) isolates were obtained, with 9.9%, 3.65, and 2.6% found in feces, eggs, and meat, respectively. Statistically, there was a significant difference between breeds (p value = 0.036). Bovines had the highest prevalence (32.83%), while Saso had the lowest (30.81%). The variation within each sample type, housing condition, and age group was not statistically significant (p value >0.05). Antimicrobial resistance was found in 29 (96.77%) of the isolates. Ampicillin and sulphamethoxazole-trimethoprim were effective against all isolates. Salmonella was isolated from various locations, sample types, ages, and breeds, indicating a wider distribution. Salmonellosis detection isolates suggested that it could be an emerging poultry and public health issue. As a result, future research should concentrate on isolating and identifying salmonella from poultry in backyard systems and comparing it to that of an intensive farm, as well as molecular characterization for serotyping and genetic studies, as well as genes responsible for salmonella pathogenicity and drug resistance.